M ‐ary Poisson reception in molecular communication. (1st April 2018) - Ankit,; Bhatnagar, Manav R.
Abstract : In this work, a mathematical modelling of M ‐ary Poisson reception processes in molecular communication (MC) environment is performed. A lower bound of the capacity of MC system is derived using maxentropic capacity‐approaching distributions; and the variation of the capacity with distance, drift velocity, and diffusion coefficient is analytically studied. Average symbol error probability (ASEP) of the considered system is analysed using maximum likelihood (ML) detection criterion. In order to improve on the error performance, an ML sequence detector employing hard decision Viterbi decoding is proposed. The proposed detection allows for a significant improvement in ASEP with some increase in system complexity.